Model Lean Halal Supply Chain pada UMKM Makanan Halal Menggunakan Lean Manufacturing dan Value Stream Mapping (VSM) (Studi Kasus: UMKM Sambal Juragan, Jawa Timur) - Muchammad Rizki Haris Maulana; Ratna Sari Dewi; Bayu Satria; Firza Agung Prakoso (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesia's halal food industry continues to grow rapidly alongside increasing Muslim consumer awareness of product halalness. However, the majority of halal food SMEs still face a dual challenge: production process inefficiency and incomplete halal assurance within their supply chains. This study aims to develop a Lean Halal Supply Chain model that integrates Lean Manufacturing particularly Value Stream Mapping (VSM) with the Halal Assurance System (HAS) at Sambal Juragan SME, East Java. The research employs a descriptive quantitative approach using a case study method. Data were collected through direct observation, in depth interviews, and process time measurements. Analysis includes waste identification using lean tools, Current State and Future State VSM mapping, Process Cycle Efficiency (PCE) calculation, and halal risk assessment using Failure Mode and Effect Analysis (FMEA) based on halal critical points. Results indicate seven dominant types of waste were identified, including a novel waste category termed halal waste. Following implementation of the proposed model, PCE improved from 42.4% to 80.1%, total lead time was reduced by 34.9%, and the average halal Risk Priority Number (RPN) decreased by 44.8%. The primary contribution of this research is the formulation of the halal waste concept as an eighth waste dimension in halal food supply chains, along with the development of a practical Lean Halal Supply Chain framework applicable to Indonesian SMEs.